2020
DOI: 10.1111/aor.13830
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of right‐left flow balance concepts for a total artificial heart

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…As reported in the two studies with patients with TAH, the difference between left and right flow can vary from 0 to 1.4 L/min 18,19 . In accordance with the previous investigation on different flow balance concepts, the interval from 0 to 1.5 L/min is selected as the target range to assess the controllability of the flow balance 28 . For each scenario, it is verified whether the target area is fully met and how many combinations of HR and RD result in the performance within the targeted area.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…As reported in the two studies with patients with TAH, the difference between left and right flow can vary from 0 to 1.4 L/min 18,19 . In accordance with the previous investigation on different flow balance concepts, the interval from 0 to 1.5 L/min is selected as the target range to assess the controllability of the flow balance 28 . For each scenario, it is verified whether the target area is fully met and how many combinations of HR and RD result in the performance within the targeted area.…”
Section: Methodsmentioning
confidence: 96%
“…In a previous study, several different concepts of right‐left flow balance regulation have been investigated 26 . It was shown that a combination of a reduced right stroke volume together with an active control of the diastole duration resulted in an adequate flow balance 28 . Compared with the left pump chamber, with an effective stroke volume of 45 mL, the stroke volume of the right pump chamber was reduced by design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this value, we also studied 60 and 175 cycles/min. In the ReinHeart TAH, the left–right circulation flow disbalance due to the pulmonary shunt is mitigated by adjusting the ratio of left and right diastole duration RD 15 . For each of the three HR values, we set the RD to 40, 45, and 50%.…”
Section: Methodsmentioning
confidence: 99%
“…The ReinHeart TAH has been previously explained in detail. 15 Briefly, it is an electrically driven TAH system with an actuator in which a piston with its alternating left and right moves empties the left and right chambers (Figure 1) into the systemic and pulmonary circulation, respectively. The reference position of the piston in time is preset in accordance with the HR.…”
Section: Pulsatile Reinheart Tah and Force Profilementioning
confidence: 99%